Semiotic Analysis of Mentos Advertisement - Damayanti, Ni Putu Wina; Devi Maharani Santika, I Dewa Ayu; Eka Pratiwi, Desak Putu (Humanis, 2021)
This study aims at analyzing the myth within the "Who Says No to Mentos" advertisement. The data of this study was taken from Mentos NG on the YouTube platform. The data were collected by documentation method with note-taking technique and analyzed by the qualitative method using the theory of Semiotic by Barthes (1972). The analysis is presented in an informal method. The results of this study show that both verbal and non-verbal signs have implied meaning to persuade and influence the audiences through visual illustration. The meaning comes from the relation between signifier and signified. This has determined that the "Who Says No to Mentos" advertisement concerned with sharing, caring, togetherness, happiness, and making friends with people in real life.